American imperialist cruelty and consequence in the scramble for Africa - Mohun, Arwen 1961- (The University of Chicago Press, 2023)
"The work of imperialism requires imperialists. But who were the everyday people who willingly served the traditional European empires? Why did they do things that ranged from thoughtless and amoral to criminal and unforgivable? With unblinking clarity and precision, Arwen Mohun here interrogates the life and actions of her great-grandfather Richard Dorsey Mohun, an American who abetted King Leopold of Belgium's horrific exploitation of the Congo Free State. Mohun details his careless and racist use of power, revealing him as an all-too-unreflective ambassador of American corporate imperialism. She seeks not to excuse Dorsey but to understand how individual desire and imperial lust fueled one another, to catastrophic ends"--
Keywords: Mohun, Richard Dorsey -- 1864-1915; Kongo; Geschichte 1882-1908; Kolonialismus; Mohun, Richard Dorsey / 1864-1915; Mohun, Richard Dorsey / 1864-1915 / Travel / Africa; Commercial agents / United States / Biography; Diplomats / United States / Biography; Explorers / Africa / Biography; Congo (Democratic Republic) / History / To 1908; Belgium / Colonies / Africa; Belgium / Colonies / Race relations; Agents commerciaux / États-Unis / Biographies; Diplomates / États-Unis / Biographies; Congo (République démocratique) / Histoire / Jusqu'à 1908; Commercial agents; Diplomats; Explorers; Race relations; Travel; Africa; Congo (Democratic Republic); United States; To 1908; Biographies; History; Biografie